Epistemic motivation affects the processing of negative emotional stimuli in interpersonal decisions - Wei, Zhenyu; Ruz, María; Zhao, Zhiying; Zheng, Yong (Frontiers in Psychology, 2015)
The present electrophysiological study investigated the role of the need for cognitive closure (NFC) in emotional processing. The NFC is conceptualized as an epistemic motive that is related to how and why people seek out information in social environments. Event-related potentials were recorded while individuals with high NFC (i.e., low epistemic motivation) or low NFC (i.e., high epistemic motivation) performed a modified Ultimatum Game, in which the emotions of happy or angry game agents were employed to predict their most likely offer. High-NFC participants more closely adhered to the decisions rules of the game than low-NFC individuals did. The electrophysiological results showed that the dispositional NFC modified early perceptual components (N170, N200, and P200). The potentials showed that high-NFC subjects had a processing bias to angry faces, whereas low-NFC individuals exhibited no such effects. These findings indicated that high-NFC individuals were more sensitive to negative emotional stimuli than low-NFC individuals in an interpersonal decision-making task.